Repurposing antiviral agents against mucormycosis - Ammar A. Khan; Nour M. AlKashef; Mohamed N. Seleem (PLoS ONE, 2026)
Mucormycosis is a life-threatening fungal infection with limited treatment options and high mortality rates among immunocompromised individuals. To identify new therapeutic strategies, we screened a library of 618 antiviral compounds against Rhizopus delemar both alone and in combination with amphotericin B (AmB) to search for agents with intrinsic antifungal activity or the ability to enhance AmB’s efficacy. Four candidates, IMB-301, U18666A, BLT-1, and obefazimod, showed potent in vitro effects, with three sustaining growth suppression comparable to AmB for up to 48 h in time-kill assays. The hepatitis C antivirals daclatasvir (DAC) and velpatasvir (VEL) demonstrated strong synergy with AmB across Mucorales isolates, lowering AmB MICs by 4- to 32-fold (ΣFICI < 0.5) and achieving fungistatic suppression of R. delemar at subinhibitory AmB concentrations (0.25 µg/mL). Importantly, neither the standalone antivirals nor their combinations with AmB reduced Vero cell viability at concentrations exceeding 4–16 × their MICs, while selectivity indices ranging from 8 to >32 indicated favorable safety margins. These findings highlight antiviral repurposing as a promising strategy to expand treatment options for mucormycosis and support further translational development.